Attenuation Function Relationship of Subduction Mechanism and Far Field Earthquake - Rozaimi, Mohd Noor; S. W., Ahmad; Azlan, Adnan; Ramli, Nazir (Asian Research Publishing Network (ARPN), 2016)
An attenuation relationship for far field earthquakes considered by subduction has been developed. The attenuation relationship function was developed using regression analysis. The database consisting of more than 130 peak ground accelerations from seven earthquake sources recorded by Seismology Station in Malaysia have been used to develop the relationship. This study aims to investigate the new relationship attenuation to gain exact peak ground acceleration at the location on site. Based on this study, the location is a structure located at Terengganu seaside. Referring to that data provided by Malaysia Meteorological Department Malaysia, an attenuation function was developed and that function can be used for earthquake prediction.